Some general results on restricted k-mean graph. (18th May 2020) - Gayathri, B.; Gopi, R
Abstract: A graph G = ( p, q ) is said to have a restricted k -mean labeling if there is an injective function f from the vertices of G to { k – 1, k, k + 1,  … , k + q – 1} such that when each edge uv is labeled with then the resulting edge labels { k, k + 1, k + 2,  … , k + q – 1} are all distinct where k is a positive integer greater than or equal to one. A graph that admits a restricted k -mean labeling is called a restricted k -mean graph.